Mengembangkan Aspek Kognitif Anak Dalam Mengenal Lambang Bilangan Menggunakan Model Problem Based Learning, Model Numbered Head Together Dengan Media Puzzle Angka Pada Kelompok A Paud Permata Bunda Mali-Mali - Faizah Hilawati (CV. ITTC INDONESIA, 2025)
Hilawati, Faizah. 2025. Developing Children's Cognitive Aspects in Recognizing Number Symbols Using the Problem-Based Learning Model, Numbered Head Together with Number Puzzle Media in Group A of Permata Bunda Mali-Mali Preschool. Thesis, Undergraduate Program in Early Childhood Education Teacher Education, Faculty of Teacher Training and Education, Lambung Mangkurat University, Banjarmasin. Supervisor: Dr. Novitawati, S. Psi., M. Pd. The selection of this research topic is driven by the importance of developing early childhood cognitive skills in recognizing numerical symbols, which serve as the foundation for arithmetic abilities and mathematical concept comprehension at later stages. At PAUD Permata Bunda Mali-Mali, some children still experience difficulties in distinguishing and memorizing numerical symbols due to limited variation in teaching methods and minimal use of engaging learning media. To address this issue, this study applied a combination of the Problem Based Learning (PBL) and Numbered Head Together (NHT) models, supported by the use of Number Puzzle media. This research employed a classroom action research (CAR) approach conducted in two cycles, consisting of planning, implementation, observation, and reflection stages. The study involved 23 children from Group A at PAUD Permata Bunda Mali-Mali (19 boys and 4 girls). Data were collected through observation, interviews, documentation, and assessments of children’s cognitive development. The data were analyzed using qualitative descriptive methods and cross-tabulation, and presented in tables, graphs, and percentages. The findings revealed a substantial improvement in children’s engagement, increasing from 8.69% in the first meeting to 82.60% in the fourth meeting. Cognitive skills also improved remarkably, rising from 13% in the “Not Yet Developed” category to 95.6% in the “Very Well Developed” category. Teacher performance was rated “very good,” successfully creating an active, enjoyable learning environment that fostered collaboration and critical thinking. In conclusion, the integration of PBL and NHT models with Number Puzzle media significantly enhanced children’s learning participation and cognitive development. It is recommended that early childhood educators adopt problem-based and collaborative learning strategies combined with educational media such as Number Puzzles to create interactive, motivating, and effective learning experiences.